Balcony atop the Entrance Gateway of the Bhandasar Temple - Temples of India Project Team (Jio Institute, 2024)
Seen here is the balcony atop the entrance gateway of the Bhandasar Temple. This balcony is semi-open with slender pilasters and a Bengal arch roofing. The ornamental cartouches on the small walls of the balcony are a feature of Rajput architecture.